Analysis of Partnership Satisfaction Between Andini Luhur Cooperative and Dairy Farmers - Eva Maulida; Siwi Gayatri; Wiludjeng Roessali (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The partnership program between dairy farmers in Getasan district and Andini Luhur Cooperative needs to be followed up because it is considered unfavorable for farmers during the period of partnership. This study aimed to analyze the partnership activities and satisfaction level of dairy farmers in Getasan District in implementing partnerships with Andini Luhur Cooperative. This research was conducted in December 2019 to January 2020 in Getasan District, Semarang Regency. The location of the study was determined purposively with the consideration that Getasan District is the center of dairy cows in Semarang Regency. The research method used was surveying method. Determination of respondents was done by taking all dairy farmers in Getasan District who were in partnership with Andini Luhur Cooperative. Data collection methods used were interviews, questionnaires, and observations. Data analysis methods used were descriptive and quantitative analysis using the Importance Performance Analysis (IPA) and Consumer Satisfaction Index (CSI) methods. Based on the results, it was found that the type of partnership is contract farming with core-plasma pattern. The results of IPA shows that there are 1 attribute that is classified in Quadrant I (top priority), 2 attributes are classified in Quadrant II (maintained), 4 attributes are classified in Quadrant III ( low priority) and 3 attributes are classified in quadrant IV (excessive). From CSI calculations, the result obtained is 54.84%, which means farmers are quite satisfied with the performance of services provided by Andini Luhur Cooperative.